EFFECT OF SOME FACTORS ON ROOTING PERCENTAGE AND SUBSEQUENT GROWTH OF MANZANILLO OLIVE CUTTINGS - Nabil M. Ameen Al-Imam (Mesopotamia Journal of Agriculture)
Two separate factorial experiments were conducted during 2004 and 2005 seasons to study rooting and subsequent growth of Manzanillo olive cuttings. The first one study of seven dates of cuttings collection from (1st January to 1st July), monthly intervals and cutting position on the shoot (terminal with 2-3 mm, median with 4-5 mm and basal with 6-8 mm in diameter). While the second experiment include study three dates of cuttings collection (1st April to 1st June), monthly intervals, cutting position on the shoot (median with 3-5 mm and basal with 6-8 mm in diameter), and soaking the cuttings in 4 concentrations of IBA solution 0, 1000, 2000 and 3000 mg.l-1 for 5 seconds. The results revealed that the maximum rooting percentage and number of roots per cutting (65.10% and 14.10 respectively) were on basal cuttings which were collected on the 1st of May in the first experiment. While the semi-hardwood basal cuttings with 6-8 mm in diameter which have been collected on the 1st of May and treated with 3000 mg IBA.l-1 showed superior rooting percentage, roots number per cutting, root length and shoot length (87.30%, 24.50, 11.40 cm and 10.30 cm respectively) in the second experiment